2004
DOI: 10.1086/422196
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography of Y-Chromosome Haplogroup I Reveals Distinct Domains of Prehistoric Gene Flow in Europe

Abstract: To investigate which aspects of contemporary human Y-chromosome variation in Europe are characteristic of primary colonization, late-glacial expansions from refuge areas, Neolithic dispersals, or more recent events of gene flow, we have analyzed, in detail, haplogroup I (Hg I), the only major clade of the Y phylogeny that is widespread over Europe but virtually absent elsewhere. The analysis of 1,104 Hg I Y chromosomes, which were identified in the survey of 7,574 males from 60 population samples, revealed sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
257
2
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 257 publications
(292 citation statements)
references
References 41 publications
20
257
2
3
Order By: Relevance
“…The high frequency and diversity found for it in Pyrenean populations (Lopez-Parra et al, 2009) seems to confirm that hypothesis. However, in contrast to I-M253, I-M26 has an extremely low frequency in Scandinavia and most probably had a minor role in the recolonization of this region (Rootsi et al, 2004).…”
Section: Phylogeographic Analysismentioning
confidence: 78%
See 2 more Smart Citations
“…The high frequency and diversity found for it in Pyrenean populations (Lopez-Parra et al, 2009) seems to confirm that hypothesis. However, in contrast to I-M253, I-M26 has an extremely low frequency in Scandinavia and most probably had a minor role in the recolonization of this region (Rootsi et al, 2004).…”
Section: Phylogeographic Analysismentioning
confidence: 78%
“…However, Y-chromosome analysis of Iberia pointed to the I-M26 subclade as the most prevalent there (Flores et al, 2004;Alonso et al, 2005;Lopez-Parra et al, 2009). It has been suggested that a region of Iberia-Southern France could be the origin of this subclade (Rootsi et al, 2004). The high frequency and diversity found for it in Pyrenean populations (Lopez-Parra et al, 2009) seems to confirm that hypothesis.…”
Section: Phylogeographic Analysismentioning
confidence: 95%
See 1 more Smart Citation
“…B 282: 20150339 (L281) [40], which has been found in the extant Sardinian population [57]. Haplogroups I1 and I2a1 are most frequent in present-day populations of Europe, with the highest frequencies in Scandinavian [58][59][60] and southeast European populations, respectively [58]. We used PCA and genetic distance maps to identify affinities of the Carpathian Basin samples with 49 516 NRY SNP profiles from present-day Eurasian and African populations (electronic supplementary material).…”
Section: (B) Y Chromosomal Dnamentioning
confidence: 99%
“…[1][2][3][4][5] The International Society of Genetic Genealogy 10 has aggregated these variants and those discovered with previous technologies into a public resource that population surveys can leverage to further elucidate the geographic origins of and structure within haplogroups. [6][7][8][9][10][11][12][13] Y-chromosome haplogroup R (hg R) is one of 20 that comprise the standardized global phylogeny. 14 It consists of two main components: R1-M173 and R2-M479 15 (Figure 1).…”
Section: Introductionmentioning
confidence: 99%